2023
DOI: 10.3926/jotse.1740
|View full text |Cite
|
Sign up to set email alerts
|

Use of gamification in English learning in Higher Education: A systematic review

Abstract: Digital gamification is a dynamic technique for enhancing English learning and closing the barrier across student learning and pedagogical praxis. The review offers a summary of gamification in digital English learning environments. In addition, this review investigates the learning experiences and outcomes of foreign language students using gamification. For this study, 18 articles published between 2014 and March 2021 were analyzed to highlight the key characteristics of this research topic. Studies have dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Gamification of education is an innovative pedagogical approach for improving learners' motivation and engagement in educational settings by combining game design features (Dichev and Dicheva, 2017;De La Cruz et al, 2023;Gutiérrez-Colón et al, 2023). The mediating roles of learners' preferences illustrated the need for autonomy and independence during learning to increase individual performance and experience (Wang et al, 2023;Nguyen et al, 2023).…”
Section: The Role Of Motivation In Gamifying the Language Classroommentioning
confidence: 99%
See 1 more Smart Citation
“…Gamification of education is an innovative pedagogical approach for improving learners' motivation and engagement in educational settings by combining game design features (Dichev and Dicheva, 2017;De La Cruz et al, 2023;Gutiérrez-Colón et al, 2023). The mediating roles of learners' preferences illustrated the need for autonomy and independence during learning to increase individual performance and experience (Wang et al, 2023;Nguyen et al, 2023).…”
Section: The Role Of Motivation In Gamifying the Language Classroommentioning
confidence: 99%
“…Ideally, gamification introduces the students to the big picture, part of a revolution that creates individual resilience to surmount learning difficulties. This insight is crucial for foreign language/English language learning because motivation has been frequently related to gamified learning (Werbach and Hunter, 2012;Gibson et al, 2015;Bovermann and Bastiaens, 2020;De La Cruz et al, 2023).…”
Section: The Role Of Motivation In Gamifying the Language Classroommentioning
confidence: 99%
“…Nowadays, gamification in online education is completely clear to anyone [23,24]. Gamification has been applied in a wide range of scientific fields, such as neurosurgery education [25], management education [26], engineering education [27], teaching in sports values [28], architecture education [29], accounting education [30], vocational technical education [31], pharmacy education [32], medical education [33], computer science education [34] historical education [35], historical heritage education [28], language learning [36,37], culture, and art [38]. As a result, the size and scope of the research, as well as the quantity of publications published in this area, have all grown.…”
Section: Introductionmentioning
confidence: 99%
“…Its adoption as a medium of instruction is driven by the belief that language proficiency equips learners with skills that are highly valued in the global job market as an effort to improve socio-economic mobility and international competitiveness (Maramag-Manalastas & Batang, 2018). In fact, a survey conducted among United Nations members revealed that most of its samples expressed approval for adopting English as the language used in their embassies (Ortiz, 2013 as cited in Laura-De La Cruz et al, 2023).…”
Section: Introductionmentioning
confidence: 99%